2019
DOI: 10.11646/phytotaxa.392.1.8
|View full text |Cite
|
Sign up to set email alerts
|

Reappraisal of Tashiroea as a genus independent of Bredia (Melastomataceae) based on molecular data

Abstract: Molecular phylogenetic analyses using ITS sequences were used to reconsider the taxonomic validity of Bredia okinawensis, B. yaeyamensis, and B. sinensis as an independent genus Tashiroea. The result showed that the three species formed a different phylogenetic lineage from other species of Bredia including its type species. We suggest that B. okinawensis, B. yaeyamensis, and B. sinensis should be treated as T. okinawensis, T. yaeyamensis, and T. sinensis, respectively, following Ito and Matsumura (1899) and D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…These findings are strongly corroborated by our chloroplast phylogenomic analyses (unpublished), indicating that the Tashiroea clade is an independent lineage distantly related to the Bredia clade. The same conclusion is also reached in a recently published study, although based on limited sampling of species (Kokubugata et al 2019). Continued use of the non-monophyletic Bredia may hinder further study of this group and cause problems in describing new species, which has led us to update its circumscription.…”
Section: Introductionsupporting
confidence: 83%
“…These findings are strongly corroborated by our chloroplast phylogenomic analyses (unpublished), indicating that the Tashiroea clade is an independent lineage distantly related to the Bredia clade. The same conclusion is also reached in a recently published study, although based on limited sampling of species (Kokubugata et al 2019). Continued use of the non-monophyletic Bredia may hinder further study of this group and cause problems in describing new species, which has led us to update its circumscription.…”
Section: Introductionsupporting
confidence: 83%
“…Several instances are recognized where different closely related taxa are distributed and have undergone differentiation across various regions of the Ryukyu Islands. Tashiroea okinawensis / T. yaeyamensis (Melastomataceae) exhibits shallow differentiation in the Ryukyu region, with closely related species found on the Chinese mainland 25 . Viola iwagawae / V. tashiroi (Violaceae) show minor differentiation in this area 26 .…”
Section: Discussionmentioning
confidence: 99%
“…The group has a complicated taxonomic history with several small genera segregated and combined through the years (Cellinese 1997, Cellinese 1998. Recent phylogenetic analyses have shown that most of the currently recognized Old World genera are not monophyletic and the tribe is in dire need of a new taxonomic arrangement (Cellinese 1998, Kokubugata et al 2019, Zhou et al 2019a, Zhou et al 2019b. In light of these issues we have opted for separating the genera geographically and then order them alphabetically until the taxonomy is updated.…”
Section: Sonerileaementioning
confidence: 99%